Angiotensin receptor blockers and risk of dementia: cohort study in UK Clinical Practice Research Datalink. (February 2015) - Goh, Kah L.; Bhaskaran, Krishnan; Minassian, Caroline; Evans, Stephen J. W.; Smeeth, Liam; Douglas, Ian J.
<x xml:space="preserve">Abstract</x> Aims This was a cohort study to evaluate whether individuals exposed to angiotensin receptor blockers have a reduced risk of dementia compared with those exposed to angiotensin‐converting enzyme inhibitors. Methods The study included new users of angiotensin receptor blockers or angiotensin‐converting enzyme inhibitors (from 1995 to 2010) from UK primary care practices contributing to the Clinical Research Practice Datalink. The association between exposure to angiotensin receptor blockers and the risk of incident dementia was analysed using a Cox model, adjusting for age, sex, body mass index, diabetes, hypertension, heart failure, statin use, socioeconomic status, alcohol, smoking, number of consultations and calendar year. Results A total of 426 089 persons were included in the primary analysis, with 45 541 persons exposed to angiotensin receptor blockers and the remainder to angiotensin‐converting enzyme inhibitors. The total number of new diagnoses of dementia was 6517. There was weak evidence of a decreased risk of dementia with exposure to angiotensin receptor blockers, with follow‐up beginning at 1 year after the start of treatment (adjusted hazard ratio 0.92, 95% confidence interval 0.85–1.00). An analysis restricted to the first 12 months after the index date showed a larger effect on dementia risk (adjusted hazard ratio 0.60, 95% confidence interval 0.50–0.72). Conclusions A small reduction in dementia risk was seen with angiotensin receptor blockers in comparison to angiotensin‐converting enzyme inhibitors. However, the strongest association was seen in early follow‐up, suggesting that the inverse association is unlikely to be causal, but instead reflects other important but unmeasured differences between angiotensin receptor blocker and angiotensin‐converting enzyme inhibitor users.